Pengaruh Fraud Hexagon terhadap Kecurangan Laporan Keuangan pada Perusahaan BUMN yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Sukartini Sukartini; Ridho Viqi (New Economy, 2026)
This study was conducted due to the persistent occurrence of financial statement fraud in State-Owned Enterprises (SOEs), which may reduce stakeholders' trust in the reliability of financial information. The study aims to examine the effect of external pressure, ineffective monitoring, auditor change, board of directors change, arrogance, and collusion on financial statement fraud based on the Fraud Hexagon approach. This study employed a quantitative approach using secondary data collected from the annual reports and financial statements of SOEs listed on the Indonesia Stock Exchange during the 2019–2023 period. The study used 85 observations selected from BUMN companies listed on the Indonesia Stock Exchange during 2020–2023, and the data were analyzed using logistic regression. The results indicate that board of directors change has a positive effect on financial statement fraud, whereas external pressure, ineffective monitoring, auditor change, arrogance, and collusion have no significant effect. These findings suggest that not all elements of the Fraud Hexagon are able to explain the occurrence of financial statement fraud in SOEs. This study is expected to contribute to the existing literature and provide insights for companies and regulators in strengthening corporate governance and preventing financial statement fraud.